The Effect of Service Quality and Tax Sanctions on Service Satisfaction - Hendra Hadiwijaya; F. Febrianty (Faculty of Economic and Business, 2019)
This study aimed to analyze the effect of service quality and tax sanctions on service satisfaction and its implementation on compliance to pay personal vehicle tax. This study uses Structural Equation Modeling (SEM) as tools of analysis. The result shows that service quality affects service satisfaction, and it implies compliance with the personal vehicle tax payable compliance. Besides that, the tax sanctions affect service satisfaction, and it implies compliance with paying personal vehicle tax. Tax sanctions are a prevention tool for violations committed by taxpayers, If Service Satisfaction fails to meet expectations, and taxpayers will feel dissatisfied. If Service Satisfaction is in line with expectations, taxpayers will feel satisfied. If Service Satisfaction exceeds expectations, taxpayers will be very satisfied.JEL Classification: K34, M31